HUBUNGAN SELF-EFFICACY SISWA TERHADAP KETERAMPILAN BERPIKIR KRITIS MATEMATIS SISWA SMP PADA MATERI BENTUK ALJABAR - Abdul Robbi Misbahudin; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2020)
The aim of the research is to find out the correlation between students' self-efficacy to mathematical critical thinking skills. The method chosen this research is a quantitative method with a correlation approach with the aim to determine the correlation and quantify the contribution of two variables, students’ self-efficacy, and mathematical critical thinking skills. The research was implemented at a junior high school (SMP) in Ngamprah District, West Bandung, with a population of all 8-grade students with 28 8-B class samples. In this research, there are two instruments used, the questionnaire instrument self-efficacy and the test instrument's critical thinking. The analysis shows that: (1) There are still students who can’t solve critical thinking questions, where students can’t understand the given problem; (2) Between students' self-efficacy and mathematical critical thinking skills don’t have a positive correlation; (3) The contribution of students' self-efficacy to mathematical critical thinking skills is 0.55% while the rest 99.45% is be affected by other factors; (4) Most students already have self-efficacy or good self-ability towards learning mathematics.